Quarks and Leptons Formation by Spontaneous Fractionation of a Pair of Elementary Heavy Fermions of Cosmological Origin (London Journal of Research In Science: Natural and Formal, 2025)
This work, based on the hypothesis of the existence of a pair of heavy fermions produced by the decay of an X-boson of cosmological origin, presents a possible mechanism for the formation of ordinary matter, which is not based on symmetry-breaking fields or massive decays on high-energy scales. The model shows that, under specific conditions, the pair of heavy fermions can spontaneously fractionate into three fermion-antifermion pairs, giving rise to the observed structure of matter. Unlike models in which leptons and quarks arise through spontaneous symmetry breaking and interactions mediated by Higgs fields, this model shows that matter could originate from a quantized electromagnetic decay process based on conservation laws and topological constraints.
Keywords: Bridge theory; charge fractionation; hadrons; leptons; matter-antimatter Asymmetry.